Phonological Errors in BIPA Learners' Speech During the Handai Indonesia Festival: A Study Based on the BIPA Kemdikbud YouTube Channel - Wijayanti, Natasya Dwi; Budiawan, Raden Yusuf Sidiq; Andrian, Setia Naka (Journal of Educational Sciences, 2025)
Phonological errors are one of the main challenges in learning Indonesian as a Foreign Language (BIPA). This study aims to describe the phonological errors made by BIPA learners during the Handai Indonesia Festival on the BIPA Kemdikbud YouTube channel. Using a mixed-methods approach, data were collected through observation and note-taking techniques, then analyzed based on the identified phonological error patterns. The results indicate that out of 144 phonological error data points, phoneme substitution was the most dominant type of error (95 occurrences), followed by phoneme addition (25 occurrences) and phoneme omission (24 occurrences). These errors were primarily caused by first-language interference, with learners from Egypt and China exhibiting significantly higher error rates compared to learners from other countries. The implications of this study highlight the need for more adaptive phonology teaching methods in BIPA programs. Currently, phonological aspects receive less attention compared to grammar and vocabulary. Further research is recommended to explore the effectiveness of these strategies in reducing phonological errors and improving BIPA learners' speech intelligibility.